BOLALARNING PSIXIK RIVOJLANISHIGA O‘YINCHOQLARNING TA’SIRI - Shomurotov Ulugbek Melikboboyevich, Safaraliyeva Sevinch Shukrullo qizi, Safarova Munisa Eshmirza qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the impact of toys on the child's psyche and children's step into big life through toys, their reaction to the events around them are covered.